Grooved tanner crab Chionoecetes tanneri in the north-western Bering Sea: criteria for choosing the optimal fishing measure - A. G. Slizkin; O. Yu. Borilko; A. N. Deminov; I. A. Korneychuk (Известия ТИНРО)
Spatial and bathymetric distribution and aggregation density is considered for bathyal crabs, including the grooved tanner crab Chionoecetes tanneri, on the data of specialized deep-water trap survey and two bottom trawl surveys within the depth range of 300‒1080 m conducted by TINRO in the northwestern Bering Sea in 2019–2020. The size of grooved tanner crab is determined as 9.0–17.0 cm for the morphometrically mature males and 6.5–15.5 cm for the morphometrically immature males, by carapace width. The size of 50 % morphometric maturity is evaluated for males of Ch. Tanneri in the northwestern Bering Sea. A new fishing measure is substantiated for this population taking into account its size composition.